National estimates of case‐mix, mortality, and economic outcomes among inpatient HIV/AIDS mono‐infection and hepatitis C co‐infection cases in the US. Issue 5 (28th November 2018) - Pham, Timothy; Rathbun, R. Chris; Keast, Shellie; Nesser, Nancy; Farmer, Kevin; Skrepnek, Grant
Abstract: Rationale, aims, and objectives: To assess inpatient clinical and economic outcomes for AIDS/HIV and Hepatitis C (HCV) co‐infection in the United States from 2003 to 2014. Method: This historical cohort study utilized nationally representative hospital discharge data to investigate inpatient mortality, length of stay (LoS), and inflation‐adjusted charges among adults (≥18 years). Outcomes were analysed via multivariable generalized linear models according to demographics, hospital and clinical characteristics, and AIDS/HIV or HCV sequelae. Results: Overall, 17.8% of the 2.75 million estimated AIDS/HIV inpatient cases involved HCV from 2003 to 2014, averaging 48.5 ± 9.0 years of age and 68.0% being male. Advanced sequalae of AIDS and HCV incurred a LoS of 10.3 ± 11.9 days, charges of 88 789 ± 131 787, and a 16.9% mortality. Many cases involved noncompliance, tobacco use disorders, and substance abuse. Although mortality decreased over time, multivariable analyses indicated that poorer outcomes were generally associated with more advanced clinical conditions and AIDS‐associated sequalae, although mixed results were observed for specific manifestations of HCV. Rural residence was independently associated with a 3.26 times higher adjusted odds of mortality from 2009 to 2014 for HIV/HCV co‐infection ( P < 0.001), although not for AIDS/HCV (OR = 1.38, P = 0.166). Conclusion: Given the systemic nature and modifiable risks inherent within coinfection, more proactive screening and intervention appear warranted, particularly within rural areas.